The comparative short-term efficacy and safety of drug-coated balloon vs. drug-eluting stent for treating small-vessel coronary artery lesions in diabetic patients - Li, Kui; Cui, Kaijun; Dan, Xuechuan; Feng, Jian; Pu, Xiaobo (Frontiers in Public Health, 2022)
Purpose This meta-analysis aimed to explore the comparative short-term efficacy and safety of drug-coated balloon (DCB) vs. drug-eluting stent (DES) for treating small-vessel coronary artery lesions in diabetic patients. Methods We searched PubMed, EMBASE, the Cochrane Library, and China National Knowledgement Infrastructure (CNKI) for retrieving relevant studies regarding the comparison of DCB with DES in treating small-vessel coronary artery lesions in diabetic patients until May 31, 2022. Two independent authors screened study, extracted data, and assessed methodological quality. Then, the meta-analysis was conducted using RevMan software, version 5.4. Results We included 6 studies with 847 patients in this meta-analysis. Pooled results showed that DCB was associated with fewer major adverse cardiac events (MACE) [RR, 0.60; 95% confidence interval (CI), 0.39–0.93; p = 0.02], myocardial infarction (MI) (RR, 0.42; 95% CI, 0.19–0.94; p = 0.03), target lesion revascularization (TLR) (RR, 0.24; 95% CI, 0.08–0.69; p < 0.001), target vessel revascularization (TVR) (RR, 0.33; 95% CI, 0.18–0.63; p < 0.001), binary restenosis (RR, 0.27; 95% CI, 0.11–0.68; p = 0.005), and late lumen loss (LLL) [mean difference (MD), −0.31; 95% CI, −0.36 to −0.27; p < 0.001], but was comparable technique success rate, death, minimal lumen diameter (MLD), and net lumen gain (NLG) to DES. There was no difference in long-term outcomes between these two techniques. Conclusions This meta-analysis shows that DCB is better than DES in the short-term therapeutic efficacy and safety of small-vessel coronary artery lesions in diabetic patients. However, more studies are required to validate our findings and investigate the long-term effects and safety of DCB.